COMMUNICATION PATTERNS OF TERAS OLEH-OLEH NUSANTARA BANDAR LAMPUNG IN REALIZING EXCELLENT SERVICE DURING THE PERIOD OF JANUARY–MARCH 2026 - Febriansah Febriansah; Mike Meiranti; Immawati Asniar (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Excellent service has become a decisive factor of competitiveness in the souvenir retail sector as tourist mobility in Bandar Lampung continues to rise. Teras Oleh-Oleh Nusantara positions itself distinctively by offering souvenirs from other regions, yet internal records reveal thirty-one consumer complaints during January–March 2026, concentrated in reliability, responsiveness, and empathy, suggesting weaknesses in how the owner and employees communicate with consumers. This study describes and analyzes the communication patterns applied in delivering excellent service through a qualitative descriptive approach, drawing on in-depth interviews, observation, and documentation involving purposively chosen owner, employees, customers, and resellers, with credibility maintained through triangulation and member checking. Findings show that primary, face-to-face communication and circular, two-way communication dominate daily service interactions, whereas linear, one-way communication surfaces only occasionally in internal miscommunication. Assurance adequately meets consumer expectations, while responsiveness, reliability, and empathy still show gaps during peak hours, pointing toward the need for consistent digital updates and evenly distributed personal attention.